Optimizing School Management: The Role of Managerial Skills, Organizational Climate, and Work Motivation - Nur Afni Indasari; Khoiri, Nur; Nurkolis (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to analyse the influence of principals' managerial skills, organizational climate, and work motivation on the effectiveness of school management, examining both partial and simultaneous effects. The research employed a quantitative approach with a correlational method. The population consisted of 213 teachers, and a sample of 139 teachers was selected using Slovin’s formula and proportional random sampling technique. Data were collected through questionnaires and analysed using descriptive statistics and both simple and multiple linear regression analyses. The prerequisite tests included normality, multicollinearity, heteroscedasticity, and linearity tests. The results indicate that the principal's managerial skills have a significant partial effect on school management effectiveness, accounting for 68.9% of the variance. Organizational climate contributes 69.0%, and work motivation has a significant influence of 68.6%. Simultaneously, managerial skills, organizational climate, and work motivation have a significant impact on school management effectiveness, contributing 72.6%. These findings highlight the importance of competent leadership, a conducive organizational environment, and high work motivation in improving school management effectiveness